Kill Two Birds with One Stone: A Multifunctional Dual‐Targeting Protein Drug to Overcome Imatinib Resistance in Philadelphia Chromosome‐Positive Leukemia. Issue 13 (3rd March 2022) - Ma, Bohan; Feng, Hui; Feng, Chao; Liu, Yi; Zhang, Hailing; Wang, Jincheng; Wang, Wenjuan; He, Pengcheng; Niu, Fan
Abstract: The Bcr/Abl plays a central role in Philadelphia chromosome‐positive (Ph+) leukemia because of the constitutively activated Abl tyrosine kinase and its downstream pathways. Currently, the clinical treatment of imatinib‐resistant patients with tyrosine kinase inhibitors is severely limited by drug resistance and adverse effects. Herein, a dual‐targeting proteolysis‐targeting chimera (PROTAC) protein drug, termed PMI Bcr/Abl‐R6, is designed by engrafting an MDM2/p53 inhibition peptide sequence onto the Bcr/Abl tetramerization domain. PMI Bcr/Abl‐R6, harboring a Bcr/Abl targeting sequence and an MDM2 binding sequence, acts as a PROTAC drug in Ph+ leukemia cells. Its dual‐targeting constitution suggests that PMI Bcr/Abl‐R6 designs to target the tetramerization domain instead of the Abl kinase domain, therefore has the potential to overcome drug resistance mutations in the kinase domain. The efficient ability of PMI Bcr/Abl‐R6 is demonstrated to simultaneously induce Bcr/Abl degradation and activate the p53 pathway. PMI Bcr/Abl‐R6 has the potential to overcome drug resistance in Ph+ leukemias by multiple mechanisms. Abstract : Imatinib‐resistant Philadelphia chromosome‐positive (Ph+) leukemia treatment remains a challenge. PMI Bcr/Abl‐R6, a designed protein PROTAC (proteolysis‐targeting chimera), targets simultaneously Bcr/Abl tetramerization and p53/MDM2 interaction, both hardly "druggable" by small molecules. PMI Bcr/Abl‐R6 induces Bcr/Abl degradation, despite isoforms and resistance‐related mutations, and activates p53 pathway, providing a different drug design strategy for protein–protein interaction targets.